PSXI-19 Investigating the Relationship Between Temperament and Performance Traits in Feedlot Cattle. (30th November 2020) - Bouffiou, Jesse; Boles, Jane A; Thomson, Jennifer M
Abstract: Temperament in cattle, is defined as behavioral changes in response to humans or changes in the environment, and has been associated with reduced feed efficiency, reduced growth rate, and poor feedlot health. The objective of the study was to determine if temperament affected the performance, growth and health of feedlot cattle. One-hundred and thirty-one Angus x Simmental steers from a single ranch were sampled at a commercial feedlot in Chappell, NE. Blood samples for metabolite analysis, exit velocity, and blood lactate concentration for temperament classification were collected in addition to feedlot performance data and carcass quality measurements. The GLM and LSM procedures of SAS (SAS 9.4, 2014) were used to evaluate differences between temperament classifications. Pearson correlations were calculated between temperament and performance variables. Steers were divided into three exit velocity classifications, with fast animals (n = 27) having exit velocity greater than one standard deviation from the mean and slow animals (n = 26) having exit velocities lower than one standard deviation from the mean. Feed intake and behavior was monitored for 42 days with GrowSafe feed bunks and average daily gain, dry matter intake and residual feed intake calculated. There were significant differences between the temperament classifications of fast, medium and slow for both exit velocity and blood lactate (P < 0.0001), indicating there was a difference in responses from the classifications. Exit velocity had no effect on any of the growth parameters measured. There was a significant positive correlation between exit velocity and blood lactate (P < 0.0001). RFI was significantly correlated with exit velocity (P = 0. 051) and blood lactate (P < 0.05). This suggests that animals with higher RFI or less efficient animals had more flighty temperaments as determined by blood lactate and exit velocity.